The Decline in the Ratio of Banking Capital to Liabilities - Mitchell, Wesley C. (Quarterly Journal of Economics, 1909)
I. The decline has taken place, for the national banks, by abrupt drops in periods of business revival, with steadiness in intervening periods, 697.—Has extended to all classes of banks, 698.—Due proximately to rapid increase of deposits, with stationary capital, 699.—II. The main cause has been an increase of lawful money supplied to the banks by the general public, 703.—III. The same tendency appears in the English banks, the Canadian banks, the State banks, 708.—IV. The decline not necessarily an indication of weakness, 712.